Thermochemical Conversion of Rubber Wood Pellets via Downdraft Gasification: Syngas Composition, Heating Value Trends, and By-Product Characterization - Wana Putri Anastasya Hutasoit; Bugae Park; Bainah Sari Dewi; Wahyu Hidayat (Forest and Nature, 2025)
The increasing global energy demand, coupled with declining fossil fuel reserves, is driving the development of biomass-based renewable energy. Rubber wood (Hevea brasiliensis) is a potential biomass source due to its abundant availability from the rejuvenation of community gardens. This study aims to analyze the energy characteristics of rubber wood pellets as biomass fuel, analyze the composition of synthesis gas (syngas) and lower heating value (LHV), and the characteristics of ash (residue from the gasification process) using a downdraft gasifier. The study was conducted at the Forest Products Technology Laboratory, Faculty of Agriculture, University of Lampung, using 20 kg of rubber wood pellets as the raw material. The gasification procedure progresses through four fundamental stages, including drying, pyrolysis, combustion, and reduction, which are conducted within a downdraft gasifier system. Syngas analysis was performed using a portable infrared syngas analyzer (Gasboard G3100-P) to determine the concentrations of CO, CO2, CH4, H2, and O2. The results showed that the average composition of the syngas produced was 17.98% CO, 8.58% CO2, 1.57% CH4, 10.04% H2, and 1.78% O2. The average calorific value (LHV) was 725.81 kcal/m3 with a range of 690–775 kcal/m3. The proximate analysis results showed a moisture content of 10.93%, volatile matter 74.37%, ash content 8.60%, and fixed carbon of 6.20% in the pellet biomass, while the ash (by-product) had a moisture content of 9.58%, volatile matter 14.42%, ash content 71.61%, and fixed carbon 4.37%. The composition of the syngas produced was within the ideal range for a downdraft, indicating that rubber wood pellets have high potential as a biomass-based renewable energy fuel.